Role of iron in breath holding spells and effect of iron therapy in children - Chesti, Mohmad Saleem; Chaman, Shilakha; Nazir, Mudasir (International Journal of Contemporary Pediatrics, 2021)
Background: Breath holding spells (BHS) are paroxysmal events resulting from painful stimulus or emotional event resulting in forceful crying, occur in children’s aged between 6 months to 6 years. To assess the role of iron in breath holding spells (BHS) and to assess the efficiency of iron therapy in reducing frequency of BHS. Methods: This was a prospective, interventional study conducted at GMC baramulla. A total of 70 patients between the ages of 6 months and 5 years with breath holding spells with iron deficiency and iron deficiency anemia were studied. After giving them iron therapy for 6 and 12 weeks, they were assessed for the improvement in their anemia and its impact on the frequency of breath holding spells. Results: Seventy children with breath holding spells were studied prospectively. Forty (57.15%) cases were males and 30 (42.85%) females. There was a statistically significant rise in the hemoglobin level, serum ferritin, serum iron with 6 and12 weeks of iron therapy (p<0.001). This rise in the hemoglobin level serum ferritin and serum iron was associated with a statistically significant fall in the frequency of breath holding spells with 6 and 12 weeks of iron therapy (p<0.001). Conclusions: iron supplement is effective in reducing the frequency of breath holding spells and thus iron has role in BHS.